Diagnosis of bovine viral diarrhea virus: an overview of currently available methods - Wang, Yuting; Pang, Feng (Frontiers in Microbiology, 2024)
Bovine viral diarrhea virus (BVDV) is the causative agent of bovine viral diarrhea (BVD), which results in significant economic losses in the global cattle industry.Fortunately, various diagnostic methods available for BVDV have been established.They include etiological methods, such as virus isolation (VI); serological methods, such as enzyme-linked immunosorbent assay (ELISA), immunofluorescence assay (IFA), and immunohistochemistry (IHC); molecular methods, such as reverse transcription-polymerase chain reaction (RT-PCR), real-time PCR, digital droplet PCR (ddPCR), loop-mediated isothermal amplification (LAMP), recombinase polymerase amplification (RPA), and CRISPR-Cas system; and biosensors. This review summarizes the current diagnostic methods for BVDV, discussing their advantages and disadvantages, and proposes future perspectives for the diagnosis of BVDV, with the intention of providing valuable guidance for effective diagnosis and control of BVD disease.